MENGEMBANGKAN MEDIA VISUAL SEBAGAI UPAYA MENINGKATKAN TEACHNG SKILL DI SD/MI DENGAN METODE MICROTEACHING PADA MAHASISWA PROGRAM STUDI PGMI - Mutmainnah, Siti Nafsul; Safitri, Endang; Mufid, Abdul (Jurnal Bilqolam Pendidikan Islam, 2022)
This study discusses the effectiveness of media visual learning as an effort to improve the teaching ability of candidates Elementary School/Madrasah Ibtida'iah teacher. Because the media can encourage and Motivate students so that they can provide solutions to problems in learning. The direct learning approach is an approach that used in this study, where researchers can directly practice in delivering the material and learning objectives. This close has features structured so as to provide a teaching experience to explore the ability of prospective teaching students, in addition to the learning approach directly, researchers can find problems that may occur in class. The method used in this research is the microteaching method. This study is presented in a qualitative form from the results of observations and interview. From these approaches and methods applied to students Madrasah Ibtida'iyah Teacher Education Study Program at STAI Khozinatul Ulum Blora. It can be concluded that in order to improve students' teaching skills, prospective elementary school teachers using the microteaching method can provide a real picture as a reference to become a competent teacher candidate and professional.